Playfulness and Dementia : a Practice Guide. - Allan, Kate (Bradford Dementia Group., 2012)
Establishing playfulness as an essential component of dementia care, this positive and uplifting book will be key in changing attitudes and providing ideas for new and valuable ways of interacting and being with individuals with the condition. John Killick explores the nature of playfulness and the many ways in which it can enrich the lives of people with dementia, including as a means of maintaining relationships and communication, supporting communication and generally lifting the spirits. Specific approaches already in existence are described, including improvised drama, clowning and laught.